Measuring Real Net Output: A Proposed Index - David, Paul A. (The Review of Economics and Statistics, 1966)
HE absence of any observable flow of net in the world argues for exclusive adherence to an income-originating interpretation of the value added by particular industries or sectors. Yet, the merit of the quest for a net production measure cannot be gainsaid. The notion of splitting up gross national product into the constituent contributions made by individual sectors of the economy carries persistent appeal despite the fact that the finalgoods and services produced by many industries never actually enter the physical flow of GNP. It has motivated recent efforts by the Office of Business Economics at the Department of Commerce to construct a set of accounts showing measures of the physical volume of the gross national product originating in the various industries of the Nation, which in principle aggregate to the physical volume of obtained by deflating final expenditures.' This appeal is, of course, buttressed by the same conventions against double-counting that underlie the current dollar GNP concept. Paralleling the concern with the total economy's capacity to produce 'goods and services to satisfy final demand, there is an abiding reluctance to attribute the results of the application of factor services at all the preceding production stages to that activity which happens to come last in the sequence of fabrication. Hesitancy on thispoint is reinforced by the 'knowledge that the degree of integration varies among industries at any moment in time, as well as over the course of time within individual industries. Given variations of the latter kind, a disinclination to accept the movements of an actual physical series as an indication of the contribution made to GNP by the industry in auestion is thoroughlv reasonable. What is wanted is a measure which excludes the contribution made to the given industry's physical by inputs purchased from other industries. A measure of real net output in that sense would be entirely meaningful. Having reaffirmed the usefulness of the theoretical notion of net commodity output, it is all the more necessary to acknowledge that during an earlier exercise in conceptual tub cleaning undertaken by the writer,2 the proverbial baby seemed to slip out along with the bath water. On that occasion it was shown that the residual, or double-deflation approach to the ideal index of net output suggested by Fabricant and Geary leads to an unfamiliar and rather harrowing index number problemone which manifests itself in the appearance of negative value added estimates.3 The index number problem in question will arise even in the absence of aggregation, because the relative product and materials prices pertaining to a given industry at a specified date reflect a particular technological nexus (between the quantity of input and output) which need not be appropriate to the production conditions prevailing at some other date. Eschewing resort to the Fabricant-Geary formula, and all the difficulties of interpretation associated with the index numbers it